The association between the triglyceride–glucose index and prognosis in postoperative renal cell carcinoma patients: a retrospective cohort study - Qin, Guoliang; Sun, Zhuang; Jin, Yuxiang; Ren, Xiangguo; Zhang, Zhaocun; Wang, Shuo; Zhou, Guanwen; Huang, Kun; Zhao, Haifeng; Jiang, Xianzhou (Frontiers in Endocrinology, 2024)
Insulin resistance has been proved to be associated with RCC. However, the prognostic value of TyG index, as marker for insulin resistance (IR), is still unclear.Therefore, we conduct the research to explore the prognostic value and predictive performance of TyG index in postoperative RCC patients. Methods A total of 651 postoperative RCC patients from from January 2016 to June 2018 were enrolled in the final study. Their clinical and laboratory parameters were collected from medical records and follow up by phone. Triglyceride-glucose(TyG) index was calculated as follows: TyG = Ln[TG(mg/dL)×FBG(mg/dL)/2]. The overall-survival(OS) and disease-free-survival(DFS) were identified as the main outcomes.TyG index is independent prognostic factor for OS(HR = 2.340, 95%CI = 1.506 to 3.64, P < 0.001) and DFS(HR = 2.027, 95%CI = 1.347 to 3.051, P < 0.001) in postoperative RCC patients. Kaplan-Meier survival curves of the different TyG index level showed statistically significant differences in terms of OS and DFS(log-rank test, p < 0.0001). Besides, the TyG index was significantly associated with RCC risk factors.TyG index is significantly associated with RCC survival. The mechanisms responsible for these results may contribute to improve RCC prognosis and immunotherapy efficacy and develop new immunotherapeutic targets.